The Fornax3D project: intrinsic correlations between orbital properties and the stellar initial mass function. Issue 3 (7th June 2022) - Poci, A; McDermid, R M; Lyubenova, M; Martín-Navarro, I; van de Ven, G; Coccato, L; Corsini, E M; Fahrion, K; Falcón-Barroso, J; Gadotti, D A; Iodice, E; Pinna, F; et al.
ABSTRACT: Variations of the stellar initial mass function (IMF) in external galaxies have been inferred from a variety of independent probes. Yet the physical conditions causing these variations remain largely unknown. In this work, we explore new spatially resolved measurements of the IMF for three edge-on lenticular galaxies in the Fornax cluster. We utilize existing orbit-based dynamical models in order to fit the new IMF maps within an orbital framework. We find that, within each galaxy, the high-angular momentum disc-like stars exhibit an IMF which is rich in dwarf stars. The centrally concentrated pressure-supported orbits exhibit similarly dwarf-rich IMF. Conversely, orbits at large radius which have intermediate angular momentum exhibit IMF which are markedly less dwarf-rich relative to the other regions of the same galaxy. Assuming that the stars which reside, in the present-day, on dynamically hot orbits at large radii are dominated by accreted populations, we interpret these findings as a correlation between the dwarf-richness of a population of stars, and the mass of the host in which it formed. Specifically, deeper gravitational potentials would produce more dwarf-rich populations, resulting in the relative deficiency of dwarf stars which originated in the lower mass accreted satellites. The central and high-angular momentum populations are likely dominated by in situ stars, which were formed in the more massive host itself. There are also global differences between the three galaxies studied here, of up to ∼0.3 dex in the IMF parameter ξ. We find no local dynamical or chemical property which alone can fully account for the IMF variations.